Analysis of risk factors associated with the high incidence of amblyopia in preterm infants at the corrected gestational age of 12 months - Yiwen Cao; Ying Wang; Bian Li; Dehai Zhu; Tian Sang; Xueyan Du; Wanjun Shi; Liu Yang (BMC Pediatrics, 2023)
Abstract Objective To investigate the perinatal and in-hospital risk factors associated with the high incidence of amblyopia in preterm infants and to analyze the correlation between the amblyopia and neurodevelopment. Methods Children discharged from the neonatal intensive care unit (NICU) at 12 months of corrected gestational age were retrospectively included in this study. Ocular screening was performed in children. At the risk of amblyopia was determined according to the American Academy of Ophthalmology Guidelines for automated preschool vision screening factors. Differences in perinatal characteristics, complications during hospitalization, and treatment modalities between the two groups of children were analyzed, and multifactorial logistic regression analysis was used to identify the independent risk factors for amblyopia. The results of developmental assessment were collected retrospectively to analyze the correlation between amblyopia and various aspects of neurological development. Results A total of 128 preterm infants, 30 in the amblyopia risk group and 98 in the non-amblyopia risk group, were included in this study. Univariate analysis showed that the amblyopia risk group had lower birth weights, higher rates of asphyxia, preterm brain white matter injury, bronchopulmonary dysplasia (BPD), intraventricular hemorrhage (IVH), sepsis during hospitalization, and higher rates of treatment with pulmonary surfactant (PS), blood transfusion, invasive ventilator, and levothyroxine. Logistic regression analysis showed that BPD in the neonatal period (odds ratio [OR] 8.355, 95% confidence interval [CI] 1.492, 46.786), brain white matter injury (OR 16.742, 95% CI 0.684, 409.804), treatment with levothyroxine (OR 2.859, 95% CI 0.946, 8.639), and use of an invasive ventilator (OR 2.983, 95% CI 0.942, 9.445) were independent risk factors for amblyopia at 12 months of corrected gestational age, while the administration of glucocorticoids (OR 0.055, 95% CI 0.004, 0.737) was a protective factor. Regarding neurodevelopmental assessment, the number of infants with lagging fine motor development was greater in the amblyopia risk group. Conclusion The presence of BPD in the neonatal period, brain white matter damage in preterm infants, and use of levothyroxine and invasive ventilator were high risk factors for amblyopia. The use of glucocorticoids therapy was a protective factor. Children with risk of amblyopia had a higher rate of poor fine motor development.